Immunomodulatory Role of Dietary Thyme against Saprolegnia parasitica Infection in Cultured Nile tilapia (Oreochromis niloticus) - Al-Said, Amal A.; Abed-elaziz, Rehab A.; Badawy, Asmaa M. (Journal of Advanced Veterinary Research, 2023)
The fish industry has grown considerably worldwide, and fungal infections represent a significant aspect that increases economic losses and challenges through high mortality rates. The Egyptian aquaculture industry is particularly vulnerable to Saprolegnia parasitica, a deadly fish pathogen. Using phytobiotics as immunomodulators, antioxidants, and health promoters in aquaculture have been proven recently as an alternative strategy for banned malachite green. This research aimed to examine the thyme effect (Thymus vulgaris) on the immune status of cultured Nile tilapia against Saprolegniasis. A total of 50 fish (Oreochromis niloticus) with skin lesions were gathered from a private fish farm in Alexandria, Egypt. Skin swabs, gill swabs, and muscle tissue were obtained from each fish. After the mycological examination, results revealed that 35 isolates out of 150 examined samples (23.33%) were positive for fungal growth, of which 15 (10%) isolates were identified as Saprolegnia species. In addition, other fungi were detected; 5 (3.33%), 8 (5.33%), 4 (2.67%), and 3 (2%) isolates were identified as Penicillium species, Aspergillus flavus, Alternaria species, and Fusarium species, respectively. To evaluate the immunomodulatory effect of thyme, 300 healthy Nile tilapia fish with a mean weight of 30 Â± 5 gm were brought to be experimentally designed; they were distributed into four groups (with three replicates) and were fed on an experimental diet including 0.0, 0.5, 1.0, and 1.5 thyme oil (gm/100gm diet) continuously for two months. Then fish were infected with S. parasitica zoospores, which were thoroughly mixed with their diet. According to results, after two months of feeding, catalase (CAT), serum lysozyme activity, and total protein dramatically increased according to the levels of thyme added; the acquisition was for the group fed on a 1.5 gm/100gm diet. Additionally, the expression of interleukin-10 (IL-10) and interleukin-1Î² (IL-1Î²) in liver tissues increased similarly. Hence, it is concluded that employing thyme would improve the well-being and yield of the farmed Nile tilapia.